Bullshit and Lies? How British and Spanish Political Leaders add to Our Information Disorder - Lilleker, Darren G.; Pérez-Escolar, Marta (Javnost-The Public, 2023)
Within what is known as the post-truth era, politicians strategically trade in alternative interpretations of data, make bold populist claims and on occasions be completely dishonest for party political gains. Such practices coincide with ever-declining trust in politicians and the democratic system, a phenomenon common to both Spain and the UK. We enquire whether public mistrust is deserved exploring the extent party leaders employ misinformation as part of their strategic communication. The paper analyses falsehoods made by political leaders as determined by major fact-checking sites EFE Verifica and Newtral in Spain, and the UK’s BBC Reality Check and Full Fact. We categorise falsehoods as misinformation, alternative facts, bullshit or lies. Results show right-wing parties most responsible for all forms of falsehoods, or they are most likely to face analysis from factcheckers. Falsehoods are used by governments defending their policies, but also by oppositions to attack the government; especially alternative facts. The overwhelming majority of policy attacks based on false information are from opposition parties, particularly Spanish parties on the right. The flagrant use of bullshit and lies, while simultaneously calling out their more mainstream opponents for similar practices, poisons the notion of democratic pluralism and makes low public trust seem perfectly justified.